Experimental and computational study of the effect of momentum-flux ratio on high-pressure nozzle guide vane endwall cooling systems - Ornano, F; Povey, T (American Society of Mechanical Engineers, 2017)
High-pressure (HP) nozzle guide vane (NGV) endwalls are often characterized by highly three-dimensional (3D) flows. The flow structure depends on the incoming boundary layer state (inlet total pressure profile) and the (static) pressure gradients within the vane passage. In many engine applications, this can lead to strong secondary flows. The prediction and design of optimized endwall film cooling systems is therefore challenging and is a topic of current research interest. A detailed experimental investigation of the film effectiveness distribution on an engine-realistic endwall geometry is presented in this paper. The film cooling system was a fairly conventional axisymmetric double-row configuration. The study was performed on a large-scale, low-speed wind tunnel using infrared (IR) thermography. Adiabatic film effectiveness distributions were measured using IR cameras, and tests were performed across a wide range of coolant-to-mainstream momentum-flux and mass flow ratios (MFRs). Complex interactions between coolant film and vane secondary flows are presented and discussed. A particular feature of interest is the suppression of secondary flows (and associated improved adiabatic film effectiveness) beyond a critical momentum flux ratio. Jet liftoff effects are also observed and discussed in the context of sensitivity to local momentum flux ratio. Full coverage experimental results are also compared to 3D, steady-state computational fluid dynamics (CFD) simulations. This paper provides insights into the effects of momentum flux ratio in establishing similarity between cascade conditions and engine conditions and gives design guidelines for engine designers in relation to minimum endwall cooling momentum flux requirements to suppress endwall secondary flows.